1990
DOI: 10.1113/jphysiol.1990.sp018350
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying presynaptic inhibition through alpha 2‐adrenoceptors in guinea‐pig submucosal neurones.

Abstract: Idazoxan and yohimbine competitively antagonized the action of noradrenaline with dissociation equilibrium constants of 20 and 30 nm respectively.3. In another series of experiments, noradrenaline and somatostatin were applied locally from a pipette so that they reached presynaptic terminals but not the cell bodies or axons of the presynaptic cell: noradrenaline inhibited EPSPs by 90 % in all neurones but somatostatin had no effect. When applied locally to the cell bodies giving rise to the presynaptic fibres,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 51 publications
1
9
1
Order By: Relevance
“…Several studies have shown that -CTx GVIA reduces the release of both ACh and several neuropeptides from guinea pig enteric nerves, and diminishes fast nicotinic excitatory postsynaptic potentials (EPSPs; Lundy and Frew, 1988;Shen and Surprenant, 1990). Our findings are consistent with these studies, which suggest that -CTx GVIA-sensitive channels are present in nerve terminals in the guinea pig ileum.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have shown that -CTx GVIA reduces the release of both ACh and several neuropeptides from guinea pig enteric nerves, and diminishes fast nicotinic excitatory postsynaptic potentials (EPSPs; Lundy and Frew, 1988;Shen and Surprenant, 1990). Our findings are consistent with these studies, which suggest that -CTx GVIA-sensitive channels are present in nerve terminals in the guinea pig ileum.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that 5‐HT 1A receptors also mediate inhibition of fEPSPs in the myenteric plexus but these studies did not identify the pharmacological properties of the synaptic responses 13,14 . Similarly, it has been established that α2‐adrenergic receptors mediate presynaptic inhibition of cholinergic and non‐cholinergic synaptic transmission in the intestine and that α2 adrenergic receptor agonists inhibit fEPSPs in the enteric nervous system 11,22,23 . However, the pharmacological properties of fEPSPs inhibited by α2 adrenergic receptor agonists were not identified.…”
Section: Presynaptic Inhibition Of Fepspsmentioning
confidence: 96%
“…There has been much debate about the relative importance of potassium channel activation and inhibition of voltage‐activated calcium channels in presynaptic G i/o ‐coupled receptor‐mediated inhibition of neurotransmitter release (see e.g. Shen and Surprenant, ; Vaughan and Christie, ; Vaughan et al ., ). It would appear that μ‐opioid receptor activation can also directly inhibit the neurotransmitter release machinery independent of any effect on membrane conductances (Capogna et al ., ) given that μ‐opioid receptor activation reduced the miniature GABAergic inhibitory synaptic currents evoked by the calcium ionophore ionomycin, that is, by direct calcium entry into the nerve terminals (Capogna et al ., ; Bergevin et al ., ).…”
Section: μ‐Opioid Receptor Activationmentioning
confidence: 99%